REKOMENDASI AREA LOKASI TAPAK SUMUR EKSPLORASI PANAS BUMI MENGGUNAKAN PEMODELAN SISTEM INFORMASI GEOGRAFIS DI DAERAH PROSPEK CISOLOK-CISUKARAME, SUKABUMI, JAWA BARAT: RECCOMENDATION FOR GEOTHERMAL EXPLORATION WELLPAD AREA USING GEOGRAPHIC INFORMATION SYSTEM MODELING IN CISOLOK-CISUKARAME PROSPECT, SUKABUMI, WEST JAVA - Husin Setia Nugraha; Dadan Wildan; Rina Wahyuningsih; Reynold Tampubolon (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2023)
The use of Geographic Information System (GIS) modelling in developing geothermal resources has been widely carried out, from the initial survey and exploration to exploitation or production stages. This GIS modelling aims to delineate specific locations that are considered to have geothermal resources or are suitable for geothermal field production facilities. This study aims to obtain a map of the recommended wellpad area for the optimal geothermal exploration well drilling location by considering technical and non-technical parameters. This research was conducted in the Cisolok-Cisukarame geothermal prospect area in Sukabumi Regency, West Java Province. The map is produced by integrating eight parameters that will affect the amount of drilling costs: prospect area, slope, reservoir crest depth area, geological structure, water source, access road, settlement area, surface manifestation area, and cultural heritage area. In the early stages, buffer areas and classifications were made for these parameters with a specific range of values based on several considerations. Furthermore, spatial data integration is carried out using vector overlaying boolean operations. The result is a map of the wellpad recommendation area for geothermal exploration wells in the Cisolok-Cisukarame area, with an area of approximately 6.31 km2 (19.62% of the P90 prospect area). Using a 120-meter fishnet produces eight large cluster areas and five small cluster areas, which are suitable for wellpad of standard hole. Meanwhile, the 50-meter fishnet produces the same number of clusters and five other smaller clusters. The results of this study can be used as recommendations for areas to be used as well as footprint locations and planning for further field survey activities such as geotechnical and infrastructure surveys.